Panel cointegration: Long-run relationship between internet, electricity consumption and economic growth. Evidence from OECD countries - Kirikkaleli, Dervis; Sokri, Abderrahmane; Candemir, Mehmet; Ertugrul, Hasan Murat (Univ Nacional Autonoma Mexico, Fac Economia, 2018)
The linkage between electricity consumption, internet demand and economic growth is aimed to investigate in this study in 35 OECD countries for the period 1993-2014. Panel cointegration, Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS) and Dumitrescu-Hurlin causality tests were performed to capture the potential long-run and causal linkages among the three variables. The findings from the FMOLS and DOLS models indicate a positive linkage between electricity, internet demand and economic growth in the long-run. Results from the Dumitrescu-Hurlin causality confirm feedback causality between electricity consumption and internet demand and unilateral causality running from economic growth to electricity consumption.
Keywords: Panel cointegration; OECD; economic growth; internet; electricity consumption; long-run